Non-Intrusive Methodologies for Large Area Urban Research - Haynes, Ian; Ravasi, Thea (2023)
Non-Intrusive Methodologies for Large Area Urban Research brings together contributions from a conference held in 2021 in association with the ERC-funded 'Rome Transformed' research project. The papers address a major challenge in archaeology. Non-intrusive research in pursuit of a deeper understanding of urban areas can be both richly informative and cost-effective. Multiple successes in the field have led to an impressive array of innovative methodologies, methodologies that are frequently combined for still greater insight and impact. Geophysical surveys, the use of UAVs, the study of exposed historic structures and the exhaustive examination of archival records can all play a vital role, and the development of these data capture methodologies is of the utmost importance for the future of research. As well as advances in data capture methodologies, however, the papers also present case studies in the management of the big data generated and in the integration of different methodologies. A further strength of this collection lies in the range of site types considered. While many projects have historically pursued non-intrusive research in areas relatively clear of modern buildings, a growing number of research initiatives, such as 'Rome Transformed' are seeking to advance them in areas which remain densely occupied. Accordingly the material presented here will also be of interest to non-archaeologists working in such diverse fields as civil engineering, urban planning and physical geography.